MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SENI BUDAYA MATERI TARI DAERAH LAIN DENGAN METODE KOLABORATIF KELAS XISMK NEGERI 3 SUKAWATI - Gheahni Asti Nadhsiyah; I Nyoman Putrayasa (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This research was carried out with the aim of improving the achievement and learning achievements of class XI Dance 1 students at SMK Negeri 3 Sukawati, through the application of Collaborative Learning Methods in their educational process. Evaluation of student learning outcomes supports learning success, because increasing student learning achievement is a milestone in the success of the learning process itself. Prior to the implementation of this research, students' learning achievement was recorded as low and they faced obstacles in understanding the material provided by the teacher. The mission of this research is to increase the learning achievement of class XI Dance 1 students at SMK Negeri 3 Sukawati. The research results revealed that after the research was carried out, student learning achievement experienced a significant increase. Before the research was conducted, students' learning achievement was relatively low, where they faced difficulties in understanding the material presented by the teacher. In Cycle I, continuous improvement was recorded, although some students had not achieved the set targets. However, Cycle II showed a significant increase in student learning achievement. Based on the results of this research, we recommend teachers to adopt Collaborative Learning Methods in their learning practices and continue to develop professional skills in conducting Classroom Action Research. Thus, student learning achievement has the potential to continue to be improved and the learning process can reach a higher level of effectiveness.